2015
DOI: 10.14202/vetworld.2015.1458-1465
|View full text |Cite
|
Sign up to set email alerts
|

Can Urtica dioica supplementation attenuate mercury intoxication in Wistar rats?

Abstract: Aim:The objective of this study was to investigate the possible protective role of nettle Urtica dioica (UD) against Hg-induced toxicity.Materials and Methods:A total of 28 rats were equally divided into four groups: the control, the Hg (0.8 g HgCl2/kg in the diet), the UD (1.5 ml UD/rat by gavage), and the Hg+UD group. HgCl2 was daily dissolved in distilled water and immediately mixed with the standard diet. A solution of daily infused fresh nettle leaves in boiling water (16 g in 25 ml) was obtained and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
3
8
0
Order By: Relevance
“…Meanwhile HgCl 2 (5 mg/kg bw) treatment was followed by LE3H (0.39 mg/g bw) administration on C2 (11.16x10 6 ) was smaller than on C1 and state approach C0 (15.66x10 6 ; Table 5; Figure 5). This result is consistent with previous research, which showed that Hg caused a signi cant decrease in spermatozoa concentration, an evident stabilization of organized seminiferous tubules, and an increase in sperm counts in Urtica dioica (UD) supplemented rats [11]. HgCl 2 -treatment was also found to reduce sperm quantity, increase sperm transit time in the epididymis, and affect sperm morphology.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Meanwhile HgCl 2 (5 mg/kg bw) treatment was followed by LE3H (0.39 mg/g bw) administration on C2 (11.16x10 6 ) was smaller than on C1 and state approach C0 (15.66x10 6 ; Table 5; Figure 5). This result is consistent with previous research, which showed that Hg caused a signi cant decrease in spermatozoa concentration, an evident stabilization of organized seminiferous tubules, and an increase in sperm counts in Urtica dioica (UD) supplemented rats [11]. HgCl 2 -treatment was also found to reduce sperm quantity, increase sperm transit time in the epididymis, and affect sperm morphology.…”
Section: Discussionsupporting
confidence: 93%
“…However, the consumption of Urtica dioica, a herbal ingredient widely distributed throughout the world, can prevent markers due to HgCl 2 , especially motility and concentration of spermatozoa. The fresh nettle leaf is an inexpensive natural protective herb and plays an essential role in preventing HgCl 2 poisoning [11]. Seminal MDA concentration was previously found to be inversely linked with sperm concentration and motility [12].…”
Section: Introductionmentioning
confidence: 99%
“…The mice were assigned in a group in which PCOS was not induced (Control), a group with induced PCOS (PCOS), the PCOS mice group which was administrated 200 mg/kg nettle extract (PCOS+ 200 N) [ 41 ], the PCOS mice group which was administrated 400 mg/kg nettle extract (PCOS+ 400 N) [ 42 ], the PCOS mice group which was administrated 125 mg/kg, lutein (PCOS+ 125 L) [ 41 ], the PCOS mice group which was administrated 250 mg/kg, lutein (PCOS+ 250 L) [ 41 ], and the PCOS mice group which was administrated 200 mg/kg nettle extract and 125 mg/kg lutein (PCOS+NL). The mice were received lutein and nettle extract in gavage form daily, for the next 30 days after induction of PCOS period [ 43 ] (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“… 144 HgCl 2 (0.8 g/kg) Male wistar rats Urtica dioica 1.5 ml UD/rat GSH ↑ Fresh nettle leaves are a protective plant that can play a beneficial role in preventing Hg poisoning. 145 HgCl 2 ; (5 mg/kg b.w) Mice Piper cubeba 200mg/kg b.w CAT↑,,MDA (LPO)↓,GST↑, GSH-Px ↑ Piper Cubeba extract improves antioxidant status by increasing GSH-Px, CAT activity and GSH levels in the liver. 146 HgCl 2 ; 2 mg/kg orally single dose Mice Tribulus terrestris extract 5.0 mg/kg MDA (LPO- lipid peroxidation)↓, GST↑, Tribulus terrestris, may afford the protection against acute HgCl 2 toxicity, by reduction of free radical accumulation and GSH depletion.…”
Section: Discussionmentioning
confidence: 99%